Spreading Resiliency Making It Happen for Schools and Communities - Milstein, Mike M.; Henry, Doris Annie ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This book is dedicated to helping readers modify environments--classrooms, schools, communities--in ways that move away from resiliency depletion and toward resiliency building. The book is organized with emphasis on the concept of community. Part one, which includes the first two chapters, explores the meaning of resiliency and why it is so important for school and community well-being. Part two, which includes four chapters, addresses specific issues and strategies related to promoting resiliency for students, educators, schools, and communities. Part three includes two chapters which present strategies to help schools and communities bring their resources together in ways that support resiliency initiatives, and provides examples of communities currently engaged in this important work. The book is designed to be interactive and includes activities to assist in developing a better understanding of the concepts and strategies presented. The book concludes with 18 handouts intended to provide further information and assist in community self-evaluation. (SD)
Availability: Corwin Press, Inc., 2455 Teller Road, Thousand Oaks, CA 91320 (Library Edition, $74.95; Paperback, $32.95). Tel: 805-499-9774; Fax: 800-417-24665 (Toll Free); e-mail: order@corwinpress.com; Web site: <http://www.corwinpress.com>.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adjustment (To Environment); Change Strategies; Children; Community; Community Development; Community Involvement; Community Problems; Community Role; Coping; Educational Change; Resilience (Personality); School Community Relationship; School Role; Schools; Community Improvement Program; Community Empowerment; Books; Guides, Non-Classroom.